The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/9767113
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Mechanisms of Oleuropein in Postmenopausal Osteoporosis

Abstract: Background. Postmenopausal osteoporosis (PMOP) has a supernal morbidity rate in elderly females. Objective. To appraise the effects of oleuropein on bone densitometry, bone metabolic index, oxidative stress, and inflammatory index in PMOP. In addition, the mechanism of olive bittersweet preventing bone loss was explored. Methods. We grouped 80 salubrious female Sprague-Dawley rats into four teams: (1) sham operation team (sham, N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…Other studies reported that OLE, HTyr, and olive mill wastewater extracts elicited beneficial effects on femur bone mineral density and improved inflammatory and oxidative stress markers in an experimental model of senile osteoporosis induced by ovariectomy associated with an acute inflammation in rats [ 305 , 306 ]. More recently, a beneficial effect of OLE on bone mineral density of lumbar vertebra and left femur of ovariectomized rats was also reported by Liu et al (2022) [ 307 ]. Moreover, OLE could reduce the serum levels of IL-6 and malondialdeyde (a marker of lipid oxidation).…”
Section: Protective Effects Of Htyr and Ole Against Skeletal Muscle D...supporting
confidence: 56%
“…Other studies reported that OLE, HTyr, and olive mill wastewater extracts elicited beneficial effects on femur bone mineral density and improved inflammatory and oxidative stress markers in an experimental model of senile osteoporosis induced by ovariectomy associated with an acute inflammation in rats [ 305 , 306 ]. More recently, a beneficial effect of OLE on bone mineral density of lumbar vertebra and left femur of ovariectomized rats was also reported by Liu et al (2022) [ 307 ]. Moreover, OLE could reduce the serum levels of IL-6 and malondialdeyde (a marker of lipid oxidation).…”
Section: Protective Effects Of Htyr and Ole Against Skeletal Muscle D...supporting
confidence: 56%
“…Currently, research aimed at studying osteogenesis disorders associated with oxidative stress is a promising direction for the development of therapeutic strategies using various compounds with antioxidant properties, including antioxidants of plant origin [69][70][71][72][73]. New mechanisms of osteoporosis that depend on redox processes are discussed, such as ferroptosis of osteocytes and osteoblasts as a result of iron-dependent lipid peroxidation that occurs in diabetes mellitus.…”
Section: Oxidative Stressmentioning
confidence: 99%